Service banking : a commentary on bank services in the United Kingdom - Hanson, D. G. (London : Institute of Bankers, 1979)
This book can only scratch the surface of what in some cases are very wide subjects. It is not strictly a textbook as such and it does not set out to teach the experts anything about their own subject.
Includes index.
Includes bibliographical references: p. 311-313.
osc 19/09/2017
Loans
Keywords: Banks and banking